2010
DOI: 10.1210/jc.2010-0701
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Measurement of Anti-Müllerian Hormone in Reproductive Endocrinology

Abstract: Development of novel antibodies directed against anti-Müllerian hormone (AMH) has allowed measurement in serum and immunohistochemical assessment in tissues. AMH is secreted by granulosa cells in late preantral and small antral follicles and appears in serum in detectable and stable amounts throughout the menstrual cycle. AMH measurement allows an assessment of ovarian reserve with several advantages over other biochemical and biophysical markers. Recent research has highlighted utility in cases of premature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 108 publications
1
66
0
1
Order By: Relevance
“…Averages and standard error of the mean (SEM) are shown for each age group a yes means cyclic swelling; no means no swelling; irr means irregular swelling b Lower detection limit was 0.16 mg/ml c % of animals ovulating in the Old group is significantly higher than the % in the Young group. The Middle-aged group does not differ from the other two the present analysis, studies of this hormone in humans (Ledger 2010;Shebl et al 2011) and cynomolgus monkeys (Appt et al 2009) suggest that serum levels of AMH are a good index of the number of oocytes present in the ovary. Further study with a larger number of chimpanzees may confirm this pattern in these apes as well.…”
Section: Discussionmentioning
confidence: 43%
“…Averages and standard error of the mean (SEM) are shown for each age group a yes means cyclic swelling; no means no swelling; irr means irregular swelling b Lower detection limit was 0.16 mg/ml c % of animals ovulating in the Old group is significantly higher than the % in the Young group. The Middle-aged group does not differ from the other two the present analysis, studies of this hormone in humans (Ledger 2010;Shebl et al 2011) and cynomolgus monkeys (Appt et al 2009) suggest that serum levels of AMH are a good index of the number of oocytes present in the ovary. Further study with a larger number of chimpanzees may confirm this pattern in these apes as well.…”
Section: Discussionmentioning
confidence: 43%
“…Menopause represents the loss of ovarian reserve and is an inevitable life event for all women who live long enough. [2, 3] The timing of this life event is associated with multiple chronic diseases such as breast cancer (late menopause) and coronary heart disease, stroke, and osteoporosis (early menopause)[49]. Thus, biomarkers that can estimate ovarian reserve and the onset of menopause may also have utility in identifying women at low or high risk of common chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[3] AMH has recently emerged as a potentially useful biomarker of ovarian reserve and of the timing of future menopause. Its utility in estimating the onset of menopause has been demonstrated in regularly cycling women from Dutch, Iranian, and US cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…These reproductive disorders include polycystic ovary syndrome (PCOS) (1), irregular menses (2, 3), and subfertility (4, 5). Anti-Müllerian hormone (AMH) is a dimeric glycoprotein produced solely by ovarian follicles (6). A previous cross-sectional report has suggested that AMH concentrations were lower among reproductive-aged Chilean women with type 1 diabetes (n=66) compared to women without type 1 diabetes (n=58) (7).…”
mentioning
confidence: 99%